A Comprehensive Systematic Study on Thermoresponsive Gels: Beyond the Common Architectures of Linear Terpolymers - Constantinou, Anna P. (Polymers (Basel), 2017)
In this study, seven thermoresponsive methacrylate terpolymers with the same molar mass (MM) and composition but various architectures were successfully synthesized using group transfer polymerization (GTP). These terpolymers were based on tri(ethylene glycol) methyl ether methacrylate (TEGMA, A unit), n-butyl methacrylate (BuMA, B unit), and 2-(dimethylamino)ethyl methacrylate (DMAEMA, C unit). Along with the more common ABC, ACB, BAC, and statistical architectures, three diblock terpolymers were also synthesized and investigated for the first time, namely (AB)C, A(BC), and B(AC); where the units in the brackets are randomly copolymerized. Two BC diblock copolymers were also synthesized for comparison. Their hydrodynamic diameters and their effective pK(a)s were determined by dynamic light scattering (DLS) and hydrogen ion titrations, respectively. The self-assembly behavior of the copolymers was also visualized by transmission electron microscopy (TEM). Both dilute and concentrated aqueous copolymer solutions were extensively studied by visual tests and their cloud points (CP) and gel points were determined. It is proven that the aqueous solution properties of the copolymers, with specific interest in their thermoresponsive properties, are influenced by the architecture, with the ABC and A(BC) ones to show clear sol-gel transition.